Pengaruh Fasilitas Perpustakaan dan Pelayanan Pegawai Perpustakaan terhadap Minat Baca Mahasiswa Pendidikan Administrasi Perkantoran di Perpustakaan Pusat Unesa - Shinta Febrianti; Durinda Puspasari (Edunusa: Journal of Economics and Business Education, 2022)
The aims of this study were to analyze: 1) the effect of library facilities on reading interest in Office Administration Education students at the Unesa central library; 2) the effect of librarian services on reading interest in Office Administration Education students at the Unesa central library; 3) the effect of library facilities and librarian services on reading interest of Office Administration Education students at the Unesa central library. This research is a quantitative research. The data collection technique that used is questionnaires and interviews. The population in this study was all 2017-2019 students of Office Administration Education at the State University of Surabaya with a total of 208 students. The sample in this study was 137 students using proportional random sampling. The instrument tests that used in this study were validity test and reliability test. The data analysis techniques using: 1) classic assumption test (normality test, multicollinearity test, and heteroscedasticity test); 2) hypothesis test using multiple linear regression. The results showed that: 1) there was a significant effect of library facilities on reading interest in Office Administration Education students at the Unesa central library; 2) there is a significant effect of librarian service on the reading interest of Office Administration Education students at the Unesa central library; 3) there is a significant effect of library facilities and librarian services on reading interest of Office Administration Education students at the Unesa central library.